Reclamation of coastal wetland to paddy soils alters the role of bacteria and fungi in nitrous oxide emissions: Evidence from a 53-year reclamation chronosequence study - Chen, Cheng; Wu, Han; Li, Chuangchuang; Yin, Guoyu; Yin, Tianyu; Pan, Jiongyu; Liang, Xia; Li, Xiaofei; Zheng, Yanling; Hou, Lijun; Liu, Min (Agriculture, ecosystems & environment, 2024)
Coastal wetlands are significant sources of nitrous oxide (N2O), a potent greenhouse gas and ozone depleting agent. Land reclamation is known to change N2O emissions from coastal wetlands, but the long-term impacts on N2O sources and emissions are not well-understood. Here, we performed respiration inhibition and molecular techniques to dissect the long-term effects of coastal reclamation on bacterial, fungal and overall N2O emissions across a 53-year chronosequence of paddy soils reclaimed from coastal wetlands. Our findings showed that reclamation of coastal wetlands to paddy soils generally promoted N2O emissions in the chronosequences, despite a significant reduction in uncultivated paddy soils. The observed increase in N2O emissions was primarily attributed to an imbalance between N2O production and consumption driven by bacterial denitrifiers. Additionally, reclamation of coastal wetlands to paddy soils shifted N2O emissions from fungal to bacterial predominance in the chronosequences, with denitrification mediated by bacterial denitrifiers dominating bacterial N2O emissions. By integrating the analysis of N2O emission rates with soil physicochemical and microbiological properties, we demonstrated that the reduced salinity following coastal reclamation diminished the relative abundance of key fungal denitrifiers (e.g., Paraconiothyrium, Penicillium and Trichoderma), thus lowering the fungal contribution to N2O emissions. This study provides novel insights into the long-term influences of coastal reclamation on the sources and emissions of N2O, and enhance our knowledge of the underlying mechanisms driving these impacts, thereby contributing to improving future models of N2O emissions from coastal ecosystems under global change. [Display omitted] •Long-term impacts of coastal reclamation on N2O source and emission were explored.•Influences of coastal reclamation on N2O emission depend on reclamation types.•Coastal reclamation shifted N2O emission from fungal to bacterial dominance.•Bacterial denitrifiers mediated denitrification dominated bacterial N2O emission.•Reduction in the abundance of key fungal denitrifiers led to shift in N2O source.